2017
DOI: 10.1111/ejn.13602
|View full text |Cite
|
Sign up to set email alerts
|

Connexin36 localization to pinealocytes in the pineal gland of mouse and rat

Abstract: Several cell types in the pineal gland are known to establish intercellular gap junctions, but the connexin constituents of those junctions have not been fully characterized. Specifically, the expression of connexin36 (Cx36) protein and mRNA has been examined in the pineal, but the identity of cells that produce Cx36 and that form Cx36-containing gap junctions has not been determined. We used immunofluorescence and freeze fracture replica immunogold labelling (FRIL) of Cx36 to investigate the cellular and subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Various studies have demonstrated the presence of GJs between pinealocytes (Wolfe 1965;Taugner et al 1981;Saez et al 1991), between astrocytes (Saez et al 1991;Berthoud and Saez 1993) and between pinealocytes and astrocytes (Cieciura and Krakowski 1991). In the rat pineal gland, Cx43 and Cx26 have been identified in GJs formed between astrocytes and pinealocytes, respectively (Saez et al 1991), but also Cx36 has been identified in pinealocytes (Belluardo et al 2000;Wang et al 2017). Nonetheless, the metabolic role of the functional coupling between pinealocytes and astrocytes have not been reported.…”
mentioning
confidence: 99%
“…Various studies have demonstrated the presence of GJs between pinealocytes (Wolfe 1965;Taugner et al 1981;Saez et al 1991), between astrocytes (Saez et al 1991;Berthoud and Saez 1993) and between pinealocytes and astrocytes (Cieciura and Krakowski 1991). In the rat pineal gland, Cx43 and Cx26 have been identified in GJs formed between astrocytes and pinealocytes, respectively (Saez et al 1991), but also Cx36 has been identified in pinealocytes (Belluardo et al 2000;Wang et al 2017). Nonetheless, the metabolic role of the functional coupling between pinealocytes and astrocytes have not been reported.…”
mentioning
confidence: 99%